Medusozoan genomes inform the evolution of the jellyfish body plan - Khalturin, Konstantin; Shinzato, Chuya; Khalturina, Maria; Hamada, Mayuko; Fujie, Manabu; Koyanagi, Ryo; Kanda, Miyuki; Goto, Hiroki; Anton-Erxleben, Friederike; Toyokawa, Masaya; Toshino, Sho; Satoh, Noriyuki (Nature ecology & evolution, 2019)
Cnidarians are astonishingly diverse in body form and lifestyle, including the presence of a jellyfish stage in medusozoans and its absence in anthozoans. Here, we sequence the genomes of Aurelia aurita (a scyphozoan) and Morbakka virulenta (a cubozoan) to understand the molecular mechanisms responsible for the origin of the jellyfish body plan. We show that the magnitude of genetic differences between the two jellyfish types is equivalent, on average, to the level of genetic differences between humans and sea urchins in the bilaterian lineage. About one-third of Aurelia genes with jellyfish-specific expression have no matches in the genomes of the coral and sea anemone, indicating that the polyp-to-jellyfish transition requires a combination of conserved and novel, medusozoa-specific genes. While no genomic region is specifically associated with the ability to produce a jellyfish stage, the arrangement of genes involved in the development of a nematocyte—a phylum-specific cell type—is highly structured and conserved in cnidarian genomes; thus, it represents a phylotypic gene cluster. Genome sequencing of a scyphozoan and a cubozoan jellyfish sheds light on the genetic basis of jellyfish-specific structures and cell types.